Technology Innovation in Mechanical Engineering Using Social Strategy for Sustainable Geothermal Business - Lubis, Syaiful Bahri; Sabrina, R.; Pasaribu, Fajar; Sihite, Frans Antoni; Rahmat, Muhammad (Journal of International Conference Proceedings, 2025)
To know the important role of technology innovation in a company achieving goals to support corporate, economic, social, environment in geothermal business. Technology innovation could enhance resource assessment, resource development, resource utilization management. They could give a competitive advantage sustainable business for the company that operates among communities. The geothermal field sometimes has different types of communities, the company should have a social strategy to make sure the operation will run as well as e xpectation. This research uses qualitative methods by undertaking social mapping, observation, interviews, analysis documents, forum group discussion. Technology innovation in mechanical engineering that is applied by the company can give a competitive advantage accelerate geothermal development. Social strategy is very important for geothermal developers so that communities can have a good impact to avoid issues of economic, social, environmental. Technology innovation in the geothermal business is to choose the right power plant technology that use. By using the binary cycle power plant system, the company can sell the electricity power at a cheaper price because the grace period is shorter than others.